2019
DOI: 10.1080/23723556.2019.1600350
|View full text |Cite
|
Sign up to set email alerts
|

USP30: protector of peroxisomes and mitochondria

Abstract: In our recent publication, we describe a mechanism by which peroxisomes are protected from degradation by autophagy under basal conditions. Taking a page from mitophagy, peroxisomes also recruit the mitochondria deubiquitinating enzyme USP30 to counter the action of PEX2, the peroxisomal E3 ubiquitin ligase to regulate pexophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Interestingly, in addition to regulating mitophagy, USP30, the OMM protein, also targets to peroxisomes in a PINK1/Parkin-independent manner 265 . Overexpression of USP30 prevents pexophagy during amino acid starvation, by counteracting the action of the peroxisomal E3 ubiquitin ligase PEX2 266 , 267 ( Figure 6 B ). Therefore, an important focus for future studies of USP30 may provide new targets and tools for studying pexophagy in human health and disease.…”
Section: Pexophagy: a Mechanism For Peroxisome Turnover And Homeostasmentioning
confidence: 99%
“…Interestingly, in addition to regulating mitophagy, USP30, the OMM protein, also targets to peroxisomes in a PINK1/Parkin-independent manner 265 . Overexpression of USP30 prevents pexophagy during amino acid starvation, by counteracting the action of the peroxisomal E3 ubiquitin ligase PEX2 266 , 267 ( Figure 6 B ). Therefore, an important focus for future studies of USP30 may provide new targets and tools for studying pexophagy in human health and disease.…”
Section: Pexophagy: a Mechanism For Peroxisome Turnover And Homeostasmentioning
confidence: 99%
“…USP30, a deubiquitinating enzyme, is crucial in regulating protein stability, presenting another dimension of the molecular interplay in CC. [ 26 ] Our study extended this understanding by linking USP30‐AS1 and USP30 to the activation of the Wnt/β‐catenin signaling pathway, a pathway critical to the diagnosis and prognosis of CC. [ 27 ] We demonstrated that USP30‐AS1 and USP30 can stabilize β‐catenin protein by inhibiting its ubiquitination, further influencing CC progression.…”
Section: Discussionmentioning
confidence: 81%
“…[ 24 ] MiR‐2467‐3p, a microRNA implicated in various cancers including colorectal and nonsmall cell lung cancer, has been identified as a tumor suppressor in CC. [ 25–27 ] Our investigations revealed that USP30‐AS1 modulates USP30 expression by interacting with miR‐2467‐3p. However, intriguingly, suppression of miR‐2467‐3p did not completely revert the effects of USP30‐AS1 knockdown on USP30 expression, suggesting the involvement of additional mediators in this regulatory axis.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, hyperubiquitination occurs sequentially at different sites of mitochondria, leading to autophagy machinery and mitophagy. 4,5 Mitophagic biological processes are triggered in response to endogenous mitochondrial damage and persuaded by chemical depolarization. 6−8 Such phenomena are important in mitigating cellular damage in alcohol-induced liver toxicity, drug-induced kidney damage, neurodegeneration, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Mitophagy ensures damaged mitochondrial clearance by membrane depolarization, leading to PINK1 adherence to the mitochondrial outer membrane (MOM), thereby phosphorylating ubiquitin and thus activating ubiquitin E3 ligase and Parkin. Furthermore, hyperubiquitination occurs sequentially at different sites of mitochondria, leading to autophagy machinery and mitophagy. , Mitophagic biological processes are triggered in response to endogenous mitochondrial damage and persuaded by chemical depolarization. Such phenomena are important in mitigating cellular damage in alcohol-induced liver toxicity, drug-induced kidney damage, neurodegeneration, and so forth. , …”
Section: Introductionmentioning
confidence: 99%